(untitled) (The Journal of Plant Protection Sciences, 2023)
Mulberry (Morus sp.), the sole food plant of silkworm (Bombyx mori) is prone to several foliar diseases caused by fungi, bacteria, virus and mycoplasma. Among them, powdery mil dew (Phyllactinia corylea), leaf rust (Peridiopsora mori), Pseudocercospora leaf spot (Pseudocercospora mori), Myrothecium leaf spot (Myrothecium roridum) and sooty mold (Ascomycetes and Deutoromycetes fungi) are major foliar diseases of mulberry in the eastern and north eastern India (7,8). About 10-15% leaf yield loss occurs due to powdery mildew, leaf rust and leaf spot dis eases (3,9). Besides, these diseases also re duce leaf quality drastically leading to poor silkworm rearing. Qadri et al. (11, 12) re ported crop loss up to 54.56% and 55.59% at maximum disease severity of leaf spot and powdery mildew, respectively.